Inversion of neurovascular coupling after subarachnoid hemorrhage in vivo. Issue 11 (November 2017) - Balbi, Matilde; Koide, Masayo; Wellman, George C; Plesnila, Nikolaus
Subarachnoid hemorrhage (SAH) induces acute changes in the cerebral microcirculation. Recent findings ex vivo suggest neurovascular coupling (NVC), the process that increases cerebral blood flow upon neuronal activity, is also impaired after SAH. The aim of the current study was to investigate whether this occurs also in vivo. C57BL/6 mice were subjected to either sham surgery or SAH by filament perforation. Twenty-four hours later NVC was tested by forepaw stimulation and CO2 reactivity by inhalation of 10% CO2 . Vessel diameter was assessed in vivo by two-photon microscopy. NVC was also investigated ex vivo using brain slices. Cerebral arterioles of sham-operated mice dilated to 130% of baseline upon CO2 inhalation or forepaw stimulation and cerebral blood flow (CBF) increased. Following SAH, however, CO2 reactivity was completely lost and the majority of cerebral arterioles showed paradoxical constriction in vivo and ex vivo resulting in a reduced CBF response. As previous results showed intact NVC 3 h after SAH, the current findings indicate that impairment of NVC after cerebral hemorrhage occurs secondarily and is progressive. Since neuronal activity-induced vasoconstriction (inverse NVC) is likely to further aggravate SAH-induced cerebral ischemia and subsequent brain damage, inverse NVC may represent a novel therapeutic target after SAH.